Financial Accountability And Service Delivery In Kabale District Uganda - Fadison, Biryomumisho; Bosco, Turyasingura John; Agaba Moses; David , Kabagambe Jesse (International Journal of Management and Business Applied, 2024)
This research was conducted in Kabale District Local Government to examine the effect of financial accountability on service delivery. The predictor variables under study were funds disbursement, auditing process and record keeping systems, while service delivery was the outcome variable. The study followed a cross sectional survey. Data from 86 respondents was collected and analyzed quantitatively, complemented with qualitative analysis. Since descriptive analysis entailed description of a single variable and its attributes, frequency tables were used to present the data. At the bivariate level, a Pearson correlation matrix was conducted to ascertain the relationships between the predictor variables and the dependent variable. A linear regression model was used to fit the data. Research findings from the regression model show thatfunds disbursement(R=862), Auditing process (R=656 and records keeping systems(R=899) have a positive significance on the service delivery Kabale District local government. The main conclusion drawn from this research is that funds disbursement, auditing process and record keeping systems have a significant effect on service delivery. The study therefore recommends that there is need to put more efforts on funds disbursement, auditing process and record keeping systems for determinations of making service delivery sustainable at Kabale District Local Government.